Listening to their voices: understanding rural women’s perceptions of good delivery care at the Mibilizi District Hospital in Rwanda - Ndirima, Zack; Neuhann, Florian; Beiersmann, Claudia (BMC women's health, 2018)
Poor quality maternity care may lead to increased maternal dissatisfaction, and subsequent decreased utilization of health services or both. In a responsive health system, determining suitable delivery care, in the mother’s opinion, may lead to an improved quality of services and the mother’s satisfaction. In Rwanda, there is still limited knowledge and inadequate research regarding patient satisfaction and preferences, especially for women’s perceptions and needs during childbirth. This study captures rural women’s perception of good delivery care to understand aspects of care they consider important during childbirth.